Increased Skin Conductance Response in the Immediate Aftermath of Trauma Predicts PTSD Risk. (April 2019) - Hinrichs, Rebecca; van Rooij, Sanne J. H.; Michopoulos, Vasiliki; Schultebraucks, Katharina; Winters, Sterling; Maples-Keller, Jessica; Rothbaum, Alex O.; Stevens, Jennifer S.; Galatzer-Levy, Isaac; Rothbaum, Barbara O.; Ressler, Kerry J.; Jovanovic, Tanja
Background: Exposure to a traumatic event leads to posttraumatic stress disorder in 10% to 20% of exposed individuals. Predictors of risk are needed to target early interventions to those who are most vulnerable. The objective of the study was to test whether a noninvasive mobile device that measures a physiological biomarker of autonomic nervous system activation could predict future posttraumatic stress disorder symptoms. Methods: Skin conductance response was collected during a trauma interview in the emergency department within hours of exposure to trauma in 95 individuals. Trajectories of posttraumatic stress disorder symptoms over 12-month posttrauma were identified using latent growth mixture modeling. Results: Skin conductance response was significantly correlated with the probability of being in the chronic posttraumatic stress disorder trajectory following trauma exposure in the emergency department (r = 0.489, p < 0.000001). Lasso regression with elastic net was performed with demographic and clinical measures obtained in the emergency department, demonstrating that skin conductance response was the most significant predictor of the chronic posttraumatic stress disorder trajectory (p < 0.00001). Conclusions: This study is the first prospective study of posttraumatic stress disorder showing skin conductance response in the immediate aftermath of trauma predicts subsequent development of chronic posttraumatic stress disorder. This finding points to an easily obtained, and neurobiologically informative, biomarker in emergency departments that can be disseminated to predict the development of posttraumatic stress disorder.